2015
DOI: 10.1242/jcs.168864
|View full text |Cite
|
Sign up to set email alerts
|

Cezanne regulates E2F1-dependent HIF2α expression

Abstract: Mechanisms regulating protein degradation ensure the correct and timely expression of transcription factors such as hypoxia inducible factor (HIF). Under normal O2 tension, HIFα subunits are targeted for proteasomal degradation, mainly through vHL-dependent ubiquitylation. Deubiquitylases are responsible for reversing this process. Although the mechanism and regulation of HIFα by ubiquitin-dependent proteasomal degradation has been the object of many studies, little is known about the role of deubiquitylases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 49 publications
1
60
0
Order By: Relevance
“…It has been shown that the K11-linkage-specific DUB Cezanne (OTUD7B) (Bremm et al, 2010;Mevissen et al, 2013) regulates stability of the transcription factor HIF-1α (Bremm et al, 2014) and expression levels of HIF-2α (Moniz et al, 2015). However, in this context, the exact topology of the ubiquitin signal is not yet understood.…”
Section: K11 Linkages In Heterotypic Ubiquitin Conjugates -A Powerfulmentioning
confidence: 99%
“…It has been shown that the K11-linkage-specific DUB Cezanne (OTUD7B) (Bremm et al, 2010;Mevissen et al, 2013) regulates stability of the transcription factor HIF-1α (Bremm et al, 2014) and expression levels of HIF-2α (Moniz et al, 2015). However, in this context, the exact topology of the ubiquitin signal is not yet understood.…”
Section: K11 Linkages In Heterotypic Ubiquitin Conjugates -A Powerfulmentioning
confidence: 99%
“…In addition, it has been reported that EPAS1 transcription is regulated by the IGF‐induced PI3K‐mTORC2 system promoting vascularization in neuroblastoma (Mohlin et al, ). The deubiquitylase Cezanne (also known as OTUD7B) is also involved in the regulation of HIF‐2α mRNA synthesis via E2F1, which directly binds to the EPAS1 promoter (Moniz et al, ). Finally, Nakazawa et al () has showed that HIF‐2α expression is epigenetically downregulated via class I/II HDACs, resulting in increased Anoctamin 1 (ANO1), calcium signaling, and elevated mTORC1 activity in tumors promoting sarcoma proliferation (Nakazawa et al, ).…”
Section: Hypoxia‐inducible Factor‐2mentioning
confidence: 99%
“…On one hand, E2F1 acts as an inhibitor of hepatitis B virus-mediated HCC by activating p53 expression [18, 19]. In animal models, the TFDP3/E2F1 pathway induces apoptosis in HCC by positively regulating HIF-2α, and the decreased levels of HIF-2α were associated with lower overall survival of HCC animals [20, 21]. On the other hand, overexpression and genome amplification of E2F1 has been observed in HCC [17, 22].…”
Section: Introductionmentioning
confidence: 99%